Studi Literatur Penggunaan Sensor untuk Sistem Deteksi Gempa - Kurniawati, Rizki; Murti, Muhammad Ary (Proceedings Series on Physical & Formal Sciences, 2021)
As a country located among three major tectonic plate confluences, namely the Eurasian Plate, the Indo-Australian Plate, and the Pacific Plate, Indonesia is an earthquake-prone area. Information about the earthquake occurrences is distributed by the BMKG through social media, websites and television. However, it is undeniable that there are still people who do not have televisions or smartphones. Therefore, earthquake warning systems began to be widely developed. Furthermore, sensors for earthquake vibration detection have an important role in earthquake warning systems. So in this article, the author has conducted a literature study and analysis of the sensors commonly used in earthquake detection systems. This study aimed to present sensor recommendations to be used as earthquake sensors. The result of the literature study, that the author had done, is the selection of sensors is customized to the needs and budget of the project. A description of the sensor recommendations for each project has also been included in this article.